Epidemiology and Clinical Features of Typhoid Fever: Burden in Bangladesh - Sattar, AFM Arshedi; Jhora, Sanya Tahmina; Yusuf, M Abdullah; Islam, M Bodrul; Islam, M Saiful; Roy, Sushmita (Journal of Science Foundation, 2013)
Typhoid fever is a systemic infection caused by Salmonella typhi or by the related but less virulent Salmonella paratyphi. The provision of clean water and good sewage systems led to a dramatic decrease in the incidence of typhoid in these regions. Early antibiotic therapy has transformed a previously life-threatening illness of several weeks' duration with an overall mortality rate approaching 20.0% into a short-term febrile illness with negligible mortality. Case fatality rates of 10.0-50.0% have been reported from endemic countries when diagnosis is delayed. Attack rates are highest in persons younger than 20 years or older than 70 years; however, the highest rate is found in infants. Neonates are at a greater risk to fecal-oral transmission secondary to relative decreased stomach acidity and buffering of ingested breast milk and formula. Elderly persons are at a relative greater risk to infection secondary to chronic underlying illness and weakened immunity. In endemic areas, children aged 1-5 years are at the highest risk of infection, morbidity, and mortality because of waning of passively acquired maternal antibody and a lack of acquired immunity. In young children, the clinical syndrome is often a nonspecific febrile illness that is not recognized as typhoid fever. Typhoid is usually contracted by ingestion of food or water contaminated by fecal or urinary carriers excreting S. enterica serotype typhi. It is a sporadic disease in developed countries that occurs mainly in returning traveler, with occasional point-source epidemics. In endemic areas, identified risk factors for disease include eating food prepared outside the home, such as ice cream or flavored iced drinks from street vendors, drinking contaminated water, having a close contact or relative with recent typhoid fever, poor housing with inadequate facilities for personal hygiene, and recent use of antimicrobial drugs. The infectious dose of S. enterica serotype typhi in volunteers varies between 1000 and 1 million organisms. Vi-negative strains of S. enterica serotype typhi are less infectious and less virulent than Vi-positive strains. S. enterica serotype typhi must survive the gastric acid barrier to reach the small intestine, and a low gastric pH is an important defense mechanism. DOI: http://dx.doi.org/10.3329/jsf.v10i1.16310 J Sci Foundation, January-June 2012;10(1):38-49